Relationship Five Behavioral Indicators and Healthy Living with Tuberculosis Multidrug-Resistant - Heri Mulyanto (Jurnal Berkala Epidemiologi, 2014)
Clean and healthy live behavior is closely related to the emergence of infectious diseases, including the continuation of Tuberculosis (TB) to Multidrug Resistance Tuberculosis (MDR-TB). This study is intended to determine the relationship between the 5 indicators of clean and healthy living behavior with MDR-TB in Dr. Saiful Anwar Malang Hospital. The study was conducted using a retrospective analytic design with a case-control study design. Subjects were drawn from the population using simple random sampling with a ratio of 1: 1 between cases and controls, MDR-TB patients in the MDR-TB clinic as many as 27 patients as a case group and patients who had TB treatment for at least 6 months with the results of negative acid-resistant bacteria as much as 27 patients as a control group. The variables in this study are clean and healthy living behavior, demographic variables, and MDR-TB. The results of the study were calculated using the Chi-square test with a confidence level of 95% (α = 0.05) indicating age, sex, education level, and marital status as well as the behavior of preventing additional infections not related to MDR-TB. Nutrient consuming behavior (OR = 0.25; p = 0.014), exercise behavior (physical activity) (OR = 0.16; p = 0.00), behavior using health care facilities (OR = 0.091; p = 0, 01), and the behavior of providing a healthy home environment (OR = 0.28; p = 0.03) are related to the incidence of MDR-TB. There are four variables of clean and healthy living behavior that are associated with MDR-TB so that health service facilities are advised to provide promotion of clean and healthy behavior for TB patients so that they do not continue to become MDR-TB.